An Overview of The Needs of Technology in Language Testing in Spain. (13th May 2015) - Laborda, Jesús García; Royo, Teresa Magal; Madera, Elena Bárcena
Abstract: Over the few years, computer based language testing has become prevailing worldwide. The number of institutions the use computers as the main means of delivery has increased dramatically. Many students face each day tests for well-known high-stakes decisions which imply the knowledge and ability to use technology to provide evidence of language mastery. However, this situation is not the same everywhere. While countries like the United States or the United Kingdom are spearheads of this tendency, others like Spain, lag way behind. This paper addresses the needs of use of computer based language testing in the new Spanish educational system. To do so, this paper introduces the current situation in Spain, then proceeds to do a SWOT analysis emphasizing the lacks and opportunities for language based assessments and concludes by stating the positive issues involving them.